2015
DOI: 10.1007/s00345-015-1652-y
|View full text |Cite
|
Sign up to set email alerts
|

Is there a place for virtual reality simulators in assessment of competency in percutaneous renal access?

Abstract: The PCNL-GRS in combination with the PERC Mentor™ simulator was able to differentiate between competent and non-competent PGTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…Few studies were found on assessment of PCA skills. 12,13 The biological bench models used porcine or bovine kidneys wrapped within foam, 14 foam in a mannequin, 15 silicone, 16 chicken carcass, 17,18 full-thickness skin flap, 19,20 or additional subcutaneous fascia, muscle, 21 and ribs. 22 Other nonbiological bench models used prototyping or 3D printing.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Few studies were found on assessment of PCA skills. 12,13 The biological bench models used porcine or bovine kidneys wrapped within foam, 14 foam in a mannequin, 15 silicone, 16 chicken carcass, 17,18 full-thickness skin flap, 19,20 or additional subcutaneous fascia, muscle, 21 and ribs. 22 Other nonbiological bench models used prototyping or 3D printing.…”
Section: Resultsmentioning
confidence: 99%
“…27 The PERC MentorÔ (Simbionix, Cleveland, OH) was the only VR simulator that has been validated for training and assessment of PCA skills. 12,13,[28][29][30][31] However, none of these studies assessed the educational impact of PCA simulators in terms of transferring PCA skills from the benchtop to the OR. Furthermore, most of these studies did not address the validity and the cost of these simulators.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Noureldin et al [39] studied the competency of urology postgraduate trainees (PGTs) in PCA. When compared with the 21 PGTs without practice, all 5 PGTs who had practiced on the simulator were competent, performed the task with significantly shorter operative and fluoroscopy time, and had significantly higher scores and successful attempts to access renal calyces.…”
Section: Discussionmentioning
confidence: 99%